Pengelolaan Sarana Prasarana dalam Menunjang Pelayanan Jamaah Masjid Al-Ishlah Tlogosari Kulon Semarang - Farid, Miftah; Savitri, Fania Mutriara (Tadbir: Jurnal Manajemen Dakwah, 2024)
The purpose of this research is to know the condition of the facilities and infrastructure and to know the service mechanism of the Al-Ishlah Tlogosari Kulon mosque, Semarang. Facilities and infrastructure have several aspects such as: planning of infrastructure facilities, procurement of infrastructure facilities, distribution of infrastructure facilities, storage of infrastructure facilities, maintenance of infrastructure facilities, inventory of infrastructure facilities, deletion of infrastructure facilities. The results of the study show that the condition of the facilities and infrastructure at the Al-Ishlah Tlogosari Kulon Mosque in Semarang can support the congregation. Facility needs have been met and provided with good management. The service mechanism for the Al-Ishlah Mosque in Tlogosari Kulon Semarang has characteristics such as the availability of good management, the availability of good facilities and infrastructure, meeting the needs of the congregation.